Examining the Relationship Between Quality of Work Life and Organizational Culture among High School Teachers in Cambodia - Samnang Pann; Sarom Mok; Sophea Chan (International Journal of Educational Innovation and Research, 2026)
This study examined the levels of quality of work life and organizational culture among the high school teachers in Cambodia and traversed through the relationship between these two constructs, the quality of work life and organizational culture. A total partisipan of 760 high school teachers from three different representative provinces and one capital city to participate in this study. The data was collected via using a structured questionnaire made and adjusted by the researchers. The instrument easily demonstrated excellent reliability in .970 scores of Cronbach’s Alpha and its accuracy was established through the expert review, back-translation and The Index of Item Objective Congruence. The data was thoroughly analyzed and inspected using descriptive and inferential methods. The findings revealed that both quality of work life and organizational culture were at a moderate level among the high school teachers. In addition to that, a strong positive relationship was found between quality of work life and organizational culture. The findings also shown that significant positive correlations between the healthy and supportive work environment and organizational culture (r=.565, p < .001), opportunities in the workplace and organizational culture (r=.554, p < 0.001), administrative support and career development assistance and organizational culture (r=.543, p < .001), Collegial relationships and a sense of belonging within the school and organizational culture (r= .438, p < .001), and Fair and adequate salary and benefits and organizational culture (r= .372, p<,001), respectively. The results clearly highlighted the importance of applying a supportive organizational culture to boost the teachers’ quality of work life in Cambodian high schools and inform Educational Policy and Strategic Planning Policymakers and school administration should integrate on organizational culture and quality of work life to design policies enhancing teacher satisfaction, retention, and performance.